HUBUNGAN PENGETAHUAN KESEHATAN GIGI DAN MULUT DENGAN JUMLAH GIGI BERFUNGSI PADA LANSIA (STUDI DI SEKOLAH LANSIA TANGGUH, KELURAHAN MOJO, SURABAYA) - Komang Ayu Purnama Dewi; Bambang Hadi Sugito; Siti Fitria Ulfah; Sunomo Hadi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
This study aims to investigate the relationship between oral health knowledge and the number of functional teeth among older adults at the Tangguh Senior Citizens’ School in Mojo Village, Surabaya. The study employed a quantitative analytical design using a cross-sectional survey approach, with a population of 70 older adults aged 60 years and older and a sample of 60 respondents selected using the Slovin formula and simple random sampling. Data were collected through a dental and oral health knowledge questionnaire—which had been validated for validity and reliability—and intraoral examinations to count the number of functional teeth. The data were then analyzed using SPSS, including descriptive statistics and Spearman’s rank correlation test. The results showed that the majority of respondents had “poor” knowledge (58.3%) and fewer than 20 functional teeth (78.3%), with a significant positive correlation (r = 0.707, p < 0.05) between better knowledge and a higher number of functional teeth. In conclusion, good oral health knowledge is closely associated with a higher number of functional teeth among older adults in the study location.